In vitro and in vivo pharmacological evaluation of polygonum persicaria l. - Siddiq, Md Mahfuj Alam; Akter, Jeasmin; Kuddus, Md Ruhul; Rashid, Mohammad A (Bangladesh Journal of Botany, 2024)
The present study was designed to investigate the in vitro antioxidant, cytotoxic, anthelmintic and in vivo analgesic, anti-diarrheal, hypoglycemic and CNS anti-depressant properties of different solvent fractions of methanol extract of leaf and flower of Polygonum persicaria L., a notable medicinal plant in Bangladesh. The crude methanol extracts were partitioned separately to petroleum-ether, carbon tetrachloride, chloroform and aqueous fractions. In DPPH scavenging assay for antioxidant test, the aqueous fraction of flower extract showed maximum antioxidant activity with IC50 of 0.60 μg/ml. Most of the fractions revealed prominent lethality (LC50) against brine shrimp nauplii. The test samples also exhibited dose-dependent anthelmintic activity against Pheretima posthuma. The leaf extract and flower extract (200-and 400 mg/kg b.w.) can decrease the painful sensation in mice. Leaf extracts and flower extracts displayed 57.69 and 50% reduction of diarrhea induced by castor oil in mice, respectively. The plant samples exhibited hypoglycemic effect and CNS anti-depressant effect in mice. Based on the possibility of bioactivity, the plant can be thoroughly examined to determine its potential efficacy and to support its traditional uses. Bangladesh J. Bot. 53(3): 475-485, 2024 (September)